Managing Exchange Risk And The Impact Of The Pandemic Crisis On Algerian And Tunisia Currencies - Kaddour, Hanane; Ait, Mohamed Mourad (جامعة الوادي University of Eloued, 2021)
This study aims to address the problem of managing foreign exchange risks and currency price fluctuations resulting from being affected by various crises, noting how to manage these risks in Algeria and Tunisia considering the pandemic coronavirus crisis and trying to find possible solutions to avoid this. And among the results of this study, there are that the techniques used to cover the risk of exchange rates prevent the formation of drainage situations, where they work to guard against risk before it appears, and to deal with it while it is reached and protected from it, which is why it is very important to choose the best technique for good management of fluctuations in the exchange rate of the country, try to increase the volume of international exchanges currencies.
مقال
Keywords: Exchange rate ; risk of exchange rate ; manage the risk ; pandemic covid19 ; techniques